2004
DOI: 10.1038/nature02663
|View full text |Cite
|
Sign up to set email alerts
|

Local sleep and learning

Abstract: Human sleep is a global state whose functions remain unclear. During much of sleep, cortical neurons undergo slow oscillations in membrane potential, which appear in electroencephalograms as slow wave activity (SWA) of <4 Hz. The amount of SWA is homeostatically regulated, increasing after wakefulness and returning to baseline during sleep. It has been suggested that SWA homeostasis may reflect synaptic changes underlying a cellular need for sleep. If this were so, inducing local synaptic changes should induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

112
1,353
19
13

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,660 publications
(1,497 citation statements)
references
References 28 publications
112
1,353
19
13
Order By: Relevance
“…Firstly, decreased activity in the parietal lobes has been consistently reported in relation to enhanced motor skill learning (Seitz et al, 1990;Toni et al, 1998;Muller et al, 2002), a phenomena believe to reflect improved sequence automation. Secondly, Huber et al (2004) recently reported that daytime learning of a motor adaptation task results in a discrete increase in the subsequent amount of NREM slow-wave activity over the parietal cortex, and that this slow-wave increase was proportional to the amount of delayed learning that developed the next day; signifying a potential link between overnight plastic changes in the parietal cortex and the degree of sleep-dependent improvement. Supporting these findings, and based on our current results, we hypothesize that as learning and task optimization is improved overnight (Kuriyama et al, 2004), there is a corresponding decreased need for conscious mapping of spatial relationships between finger movements and position (Seitz et al, 1990;Toni et al, 1998;Muller et al, 2002), the consequence of which is reduced post-sleep parietal involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, decreased activity in the parietal lobes has been consistently reported in relation to enhanced motor skill learning (Seitz et al, 1990;Toni et al, 1998;Muller et al, 2002), a phenomena believe to reflect improved sequence automation. Secondly, Huber et al (2004) recently reported that daytime learning of a motor adaptation task results in a discrete increase in the subsequent amount of NREM slow-wave activity over the parietal cortex, and that this slow-wave increase was proportional to the amount of delayed learning that developed the next day; signifying a potential link between overnight plastic changes in the parietal cortex and the degree of sleep-dependent improvement. Supporting these findings, and based on our current results, we hypothesize that as learning and task optimization is improved overnight (Kuriyama et al, 2004), there is a corresponding decreased need for conscious mapping of spatial relationships between finger movements and position (Seitz et al, 1990;Toni et al, 1998;Muller et al, 2002), the consequence of which is reduced post-sleep parietal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Demonstrations of overnight, sleep-dependent learning have now been reported across both sensory (Karni et al, 1994;Gais et al, 2000;Stickgold et al, 2000a,b;Fenn et al, 2003;Atienza et al, 2004;Gaab et al, 2004) and motor (Smith and MacNeill, 1994;Fischer et al, 2002;Walker et al, 2002Walker et al, , 2003aKorman et al, 2003;Huber et al, 2004;Robertson et al, 2004;Kuriyama et al, 2004) skill memory domains.…”
mentioning
confidence: 99%
“…The search for mechanisms underlying the cognitive role of sleep showed that slow oscillations typical of non-rapid eye movement (NREM) sleep are augmented after learning 17 , are proportional to the amount of learning in preschoolers 18 and can increase learning when experimentally boosted 19 . These findings close a causal loop that relates mnemonic gain to early-sleep neural synchronization.…”
Section: R E V I E Wmentioning
confidence: 99%
“…When sleep is restricted, an enhanced SWA response follows in the next sleep period. Enhanced SWA has been associated with improved cognitive performance (Huber et al, 2004), but it is not clear whether a selective reduction of SWA is associated with decreased performance. Here we show a conditional, CNS knockout of the adenosine receptor, AdoA1R gene, selectively attenuates the enhanced SWA response to restricted sleep, but not sleep duration.…”
Section: Department Of Psychiatry Utswmentioning
confidence: 99%